Study the efficiencyof Antioxidants produced from fermented koji by Aspergillus niger on some oils - Jabir Al-Rikabi, Ali Khudhair; Al-Dubon, Abdol-Hafiz; Mohammed, Hadeel Wadi (Journal of Kerbala for Agricultural Sciences, 2014)
The antioxidative properties of EAERK were studied and were found as follows: the antioxidant activity of EAERK were varied to retard the peroxidation of linoleic acid.The scavenging effect for free radicals of EAERK was increased with concentrations increasing and the scavenging effects of BHT was higher than EAERK.The reducing power of EAERK was increased with the concentrations increasing being lower than both BHT and α-tocopherol , and the chelating ability to ferrous ion of EAERK was lower than EDTA-2Na .The total phenolic compounds of ethyl acetate extracted from rice koji fermented by A. niger S1 were 223.8 µg gallic acid / mg extract. The antioxidant stability of EAERK were studied toward many factors and were recorded as follows: EAERK was stable at neutral conditions and was unstable under both acidic and alkaline conditions.EAERK have good thermal stability characteristics and tolerated heating at 185ْ C for 2 h. EAERK showed synergistic effects with α-tocopherol and citric acid , it has been found that the synergistic effects of EAERK with α-tocopherol were higher in the inhibition of linoleic acid peroxidation system than that of citric acid.The inhibitory effect of EAERK to retard olive oil and fish oil oxidation was increased by increasing their concentrations